Development in the research of language and gender in Anglophone and Serbian literature - Babić-Antić Jelena B.; Nikolić Melina M. (Baština, 2023)
Based on the relevant foreign and domestic research and references, this article aims to offer an insight into the most prominent former and current studies in the field of language and gender studies. In this paper we attempt to present the research that shaped the field known as language and gender studies. When it comes to unequal treatment of women in society and language alike, there have been some positive changes since the seventies, especially in the Western countries. The reality is somewhat different in the Serbian society, due to the influence of persistent patriarchal norms. Moving forward in the field and searching for new and fresh research topics seems to have brought the things right back at the start. The question of male power over women and the role that gendered language plays in that process is no longer the central issue of sociolinguistic studies. Hence, some of the most prominent authors from the field are urging to turn the focus back on the issue of gender biased inequality. Having in mind everything mentioned above, it seems that there is still significant work to be done in the fields such as critical sociolinguistics, critical discourse analysis and all those fields concerned with gender issues.